Opportunity for a Healthy Campus Program as a Sustainable Development Goal: Assessing Lifestyle Factor and Mental Health Status - Heni Trisnowati; Fitri, Rika Yulianti; Rosemary, Rizanna; Nugroho, Ariyanto (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Globally, mental health has become a major issue in health development today. Campus communities cannot be separated from the problem of mental health. Aims: This study aims to describe the relationship between demographic and lifestyle factors with mental health status in campus communities. Method: This study used a quantitative method with a cross-sectional design. Data collection was conducted through an online survey on 11-30 October 2021 at one of the universities in Yogyakarta. There were 503 respondents consisting of students, lecturers, and education staff. The instrument of mental health was the Self-Reporting Questionnaire-29 (SRQ-29). Result: There were indications of needing referral due to anxiety and depression as much as 33.4%, and there were 5.28% of respondents requiring referral due to psychotic disorders, drugs, and PTSD. Demographic factors associated with mental health status were job status, sex, and age. Meanwhile, lifestyle aspects that are associated with mental health status are physical activity duration and fruit and vegetable consumption per day. This was indicated by the respective p-values of 0.000 (job status), 0.042 (sex), 0.027 (age), 0.003 (duration of physical activity), and 0.011 (consumption of fruits and vegetables per day). Furthermore, multivariate analysis showed that the duration of physical activity, as well as fruit and vegetable consumption, had a negative linear effect on the incidence of mental health disorders. Conclusion: The main findings provide baseline data for developing healthy campuses as part of sustainable development goals (SDGs), particularly for mental health programs.